Efektivitas konsumsi "iron-rich cookies" berbasis tepung biji kecipir dan modifikasi fermentasi serealia sebagai upaya penurunan prevalensi anemia defisiensi besi - Nurvitasari, Rifzi Devi; Cahyaningrum, Descha Giatri; Dinata, Gallyndra Fatkhu (JOURNAL OF Pharmacy and Tropical Issues, 2025)
Background: Iron deficiency anemia among adolescent girls is a reproductive health challenge that requires functional food interventions based on local wisdom. Purpose: To evaluate the effectiveness of a functional food intervention through the provision of "Iron-Rich Cookies" based on winged bean seeds (Psophocarpus tetragonolobus) on the hemoglobin (Hb) levels of female college students. Method: This study employed a quasi-experimental method with a pre-post test control group design involving 30 respondents randomly divided into intervention and control groups. The intervention product was processed using modified cereal fermentation to enhance mineral bioavailability. Results: The product contained 18.2 mg/100g of Iron (Fe), 16.5% protein, and 485.0 kcal of total energy. Modification through the fermentation process was proven effective in reducing phytic acid levels by 65%, reaching 145.2 mg, which optimized mineral bioavailability. Clinically, the intervention group showed a significant increase in Hb levels of 2.1 g/dL (p<0.001), compared to the control group which only increased by 0.2 g/dL. The product demonstrated high acceptability (score of 4.2) and a compliance rate of 96.7% with no reported gastrointestinal side effects. Conclusion: "Iron-Rich Cookies" are effective in significantly increasing hemoglobin levels. Utilizing the agricultural potential of winged bean seeds through the synergy of midwifery and food technology is highly recommended as an independent and sustainable preventive solution for anemia in adolescent girls.   Keyword: Anemia; Functional Food; Hemoglobin; Iron; Winged Bean.   Pendahuluan: Anemia defisiensi besi pada remaja putri merupakan tantangan kesehatan reproduksi yang memerlukan intervensi pangan fungsional berbasis kearifan lokal. Tujuan: Untuk mengevaluasi efektivitas intervensi pangan fungsional melalui pemberian "Iron-Rich Cookies" berbasis biji kecipir (Psophocarpus tetragonolobus) terhadap kadar hemoglobin (Hb) mahasiswi. Metode: Quasi-eksperimen dengan rancangan pre-post test control group design pada 30 responden yang dibagi secara acak ke dalam kelompok intervensi dan kontrol. Produk intervensi diolah dengan modifikasi fermentasi serealia untuk meningkatkan bioavailabilitas mineral. Hasil: Produk mengandung Fe sebesar 18,2 mg/100 g, protein 16,5%, dan energi total 485,0 kkal. Modifikasi melalui proses fermentasi terbukti efektif mereduksi kadar asam fitat sebesar 65% hingga mencapai 145,2 mg, yang mengoptimalkan bioavailabilitas mineral. Secara klinis, kelompok intervensi menunjukkan peningkatan kadar Hb yang signifikan sebesar 2,1 g/dL (p<0,001), dibandingkan dengan kelompok kontrol yang hanya mengalami kenaikan 0,2 g/dL. Produk ini memiliki akseptabilitas tinggi (skor 4,2) dan tingkat kepatuhan 96,7% tanpa adanya laporan efek samping gastrointestinal. Simpulan: "Iron-Rich Cookies" efektif meningkatkan kadar hemoglobin secara signifikan. Pemanfaatan potensi agraris biji kecipir melalui sinergi kebidanan dan teknologi pangan ini layak direkomendasikan sebagai solusi preventif anemia yang mandiri dan berkelanjutan bagi remaja putri.   Kata Kunci; Anemia; Biji Kecipir; Hemoglobin; Pangan Fungsional; Zat Besi.